Raymond Williams Now
VIII, 183 p.
Keywords: The work of Raymond Williams continues to exercise a powerful hold over the minds of contemporary cultural analysts and social commentators. This collection responds to the challenge of Williams's thinking in discussions of topics of current interest and concern. The essays embrace a widely-divergent field of enquiry, from the study of language, dramaturgical theory, the theory of human needs and approaches to sociology, cultural studies and television, to issues of history, temporality and the future in relation to modernity and the postmodern.